UNGKAPAN PERMINTAAN KONFIRMASI STUDI MAKNA DAN BENTUK DAROO DAN YONE - Rafi Safitri; Arza Aibonotika; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find the meaning and function of daroo and yone as the requests for confirmation in Japanese. The background to this research is the similarity between the two expressions. Data were analyzed using the theory of modality by Nitta. As the results, daroo which basically has the element of doubt as well as the meaning of a great possibility that cause requests for confirmation. As an expression of confirmation the two can replace each other depending on the degree of certainty by the speaker based on information on the proposition, interlocutor, and the situation. Daroo is difficult to replace with yone when used as a reminder. On the other hand, yone is difficult to replace with daroo when used as an affirmation of agreement or conformity with the interlocutor.Key Words: shuujoshi, modality, proposition